2016
DOI: 10.1007/s12033-016-9957-7
|View full text |Cite
|
Sign up to set email alerts
|

T7 Endonuclease I Mediates Error Correction in Artificial Gene Synthesis

Abstract: Efficacy of de novo gene synthesis largely depends on the quality of overlapping oligonucleotides used as template for PCR assembly. The error rate associated with current gene synthesis protocols limits the efficient and accurate production of synthetic genes, both in the small and large scales. Here, we analysed the ability of different endonuclease enzymes, which specifically recognize and cleave DNA mismatches resulting from incorrect impairments between DNA strands, to remove mutations accumulated in synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(41 reference statements)
5
6
0
Order By: Relevance
“…We find that the addition of T7 ligase actually decreased assembly quality relative to the no ligase control. In agreement with previous studies, we also find T7 Endonuclase I to be highly sensitive to protocol and concentration as exhibited by the wide range of error frequencies [12,14]. After T7 Endonuclease I, we found MutS to be the third most effective enzyme at 11.2 errors/kb, with T4 Endonuclease VII, Surveyor, and Endonuclease V following.…”
Section: Enzymatic Error Correction Improves Assembly Qualitysupporting
confidence: 92%
See 3 more Smart Citations
“…We find that the addition of T7 ligase actually decreased assembly quality relative to the no ligase control. In agreement with previous studies, we also find T7 Endonuclase I to be highly sensitive to protocol and concentration as exhibited by the wide range of error frequencies [12,14]. After T7 Endonuclease I, we found MutS to be the third most effective enzyme at 11.2 errors/kb, with T4 Endonuclease VII, Surveyor, and Endonuclease V following.…”
Section: Enzymatic Error Correction Improves Assembly Qualitysupporting
confidence: 92%
“…With our method tuned, we then analyzed errors in model a two-oligo assembly to assess its sensitivity. Previous studies found the most common errors in the final gene synthesis product to be either single-base deletions [11,14,19], or mismatches [12,20]. Here, we also found mismatches to be the most common error in our assembly.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Gene synthesis was used to produce 56 genes for which there was no access to a gDNA template. Artificial genes were designed with a codon usage table optimized for expression in E. coli and synthesized using standard procedures (23). Purified nucleic acids (ϳ50 ng) were subsequently cloned into pHTP9 E. coli expression vector using the NZYEasy cloning kit (NZYTech Ltd.), according to established protocols for the ligation independent cloning technology.…”
Section: Methodsmentioning
confidence: 99%